The Latest Technologies in the Development and Practical Application of Helical Blade Screw Piles in Construction - Dubinchyk, O. I.; Ilnytskyi, I. M. (Science and Transport Progress, 2025)
Purpose. The purpose of the scientific article is to study the practical application of a screw pile with a spiral blade (geoscrew) in the construction of pile foundations, as well as the practical application of the principle methodology for calculating the bearing capacity of piles of this type. Analysis and assessment of the discrepancy between the actually obtained bearing capacity of piles based on the results of tests with static vertical loads in comparison with the calculated data. Experiment and creation of certain conclusions regarding the resistance of the soil in the process of immersion of piles in the form of friction on the lateral surface, the formation of certain conclusions regarding the level of such friction. Assessment of the level of labor intensity of construction work when using piles with a spiral blade in construction. Methodology. The materials presented for studying the features of structures are created on the basis of an implemented construction project for the construction of foundations for overhead power line supports using screw piles with a spiral blade. To create such a construction object with further scientific study of the features, research program and regulatory documentation for the design of building structures were used. As a result, an alternative design was developed and analyzed in relation to standard solutions for the construction of such foundations, namely screw piles with a spiral blade, combined with a reinforced concrete monolithic grillage. Findings. Results. The relevant data on the bearing capacity of piles were obtained, data on the level of soil resistance on the lateral surface of piles during their immersion, the methodology for theoretical calculation of piles was verified by full-scale tests for compressive and pulling loads. Information was obtained on the main design and calculation difficulties in the practical immersion of piles of this type. The experience of combining piles and grillage into one structure capable of taking on large loads and providing a reliable foundation for above-ground structures was studied. Originality. First, the correspondence of the results of field tests and the results of experimental theoretical calculations of the bearing capacity of piles with a spiral blade against the soil was confirmed. Practical value. It consists in the fact that on the basis of the study of this experience, answers to previously unknown questions on the calculation of geoscrews were obtained, which in turn makes it possible to design foundations using screw piles with a spiral blade.